Water Matters : Resilient, Inclusive and Green Growth through Water Security in Latin America - World Bank (Washington, DC, 2022)
Water security is a matter of increasing concern across the world and Latin America and the Caribbean (LAC) is no exception. With rapidly growing demands for water and increasing variability due to climate change, ensuring water access to all users and mitigating water-related risks should be at the center of national and regional adaptation strategies. With nearly a third of the world's water resources, the LAC region's development has been inadvertently driven by water. This rich water endowment has allowed LAC to position itself as the world's largest net food-exporting region and greenest in terms of electricity production through hydropower. Water has played a fundamental role in reducing poverty, preserving LAC's natural wealth, and accelerating economic growth. More importantly, access to safe drinking water and sanitation services has contributed to improve the health and living conditions of millions of people. Despite this progress, there are urgent water sector challenges that threaten the region's sustainable development. Access to water and sanitation services is inequitable, with greater gaps in rural, indigenous, and peri-urban communities. In addition, water-related extremes such as floods and droughts are becoming more frequent and severe, having negative effects in lower-income communities. These gaps are more likely to be broadened by unsustainable water management practices, growing demands by competing water users, increasing pollution, and climate change impacts. In LAC, inadequate infrastructure results in a lack of storage and limited investment reduces the capacity of institutions to achieve integrated water resources management and improve service provision. The Stockholm International Water Institute (SIWI) conducts research, convenes multi stakeholder dialogues, builds institutional capacity, and provides policy advice to water decision-makers. Focused on improving water governance, the authors aim to contribute to more prosperous and inclusive societies.